2016
DOI: 10.3390/diseases4010004
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Prader-Willi Syndrome Affect Heart Rate Recovery from Dynamic Resistance Exercise in Youth

Abstract: Following exercise, heart rate decline is initially driven by parasympathetic reactivation and later by sympathetic withdrawal. Obesity delays endurance exercise heart rate recovery (HRR) in both children and adults. Young people with Prader-Willi Syndrome (PWS), a congenital cause for obesity, have shown a slower 60-s endurance exercise HRR compared to lean and obese children, suggesting compromised regulation. This study further evaluated effects of obesity and PWS on resistance exercise HRR at 30 and 60 s i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…A total of 483 studies were identified, of which 447 did not meet the inclusion criteria. Twenty‐two studies, whose details are summarized in Tables and , were finally included and evaluated (Figure ). The retrieved articles included a total of 766 subjects (356 patients with PWS [242 children and/or adolescents and 114 adults]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 483 studies were identified, of which 447 did not meet the inclusion criteria. Twenty‐two studies, whose details are summarized in Tables and , were finally included and evaluated (Figure ). The retrieved articles included a total of 766 subjects (356 patients with PWS [242 children and/or adolescents and 114 adults]).…”
Section: Resultsmentioning
confidence: 99%
“…25 With regard to blood pressure (BP), similar levels of systolic BP were found in children with or without PWS. 16,22,33 However, one study observed a higher post-exercise diastolic BP in children with PWS compared to lean and obese children without this condition (24% and 11% lower, respectively). 22 Adults with PWS showed lower values of maximal oxygen uptake (~47%) and ventilatory threshold (~44%) than overweight and obese adults without PWS.…”
Section: Acute Response To Exercisementioning
confidence: 97%
See 3 more Smart Citations